2010
DOI: 10.1094/mpmi-23-4-0415
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Evolutionary Analyses of Pseudomonas syringae pv. tomato Race 1

Abstract: Pseudomonas syringae pv. tomato, the causal agent of bacterial speck of tomato, has recently become an increasing problem in California due to the evolution and prevalence of highly aggressive race 1 strains. In resistant plant genotypes, the type III effectors AvrPto and AvrPtoB are recognized by the tomato proteins Pto and Prf. We investigated the prevalence of avrPto and avrPtoB in strains collected over the last 13 years in California. All race 1 strains retained avrPtoB but did not express AvrPtoB protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 56 publications
4
62
0
Order By: Relevance
“…This method of crop protection has been actively used by geneticists, breeders, and farmers for over 100 y. However, whereas some R proteins have been effective in the field for decades, others were defeated in a single season (1,2). Our inability to a priori predict which R proteins will confer broad spectrum, durable resistance is a major limitation to crop improvement efforts and stems from an incomplete understanding of the genomic diversity present in a pathogen population.…”
Section: P-eif2αmentioning
confidence: 99%
“…This method of crop protection has been actively used by geneticists, breeders, and farmers for over 100 y. However, whereas some R proteins have been effective in the field for decades, others were defeated in a single season (1,2). Our inability to a priori predict which R proteins will confer broad spectrum, durable resistance is a major limitation to crop improvement efforts and stems from an incomplete understanding of the genomic diversity present in a pathogen population.…”
Section: P-eif2αmentioning
confidence: 99%
“…Thus, the selection pressure may have forced plants to evolve the Pto gene encoding a protein that is recalcitrant to the E3 ligase activity of AvrPtoB and capable of recognizing two different domains in the N terminus of AvrPtoB to activate ETI (Martin, 2012;Mathieu et al, 2014). However, a previous study of the avrPtoB gene from the Pst strain T1 ) and a more recent study of Pst race 1 strains collected from the fields of California indicated that Pst may have evolved a mechanism to reduce the accumulation of AvrPtoB to escape host detection by Pto while preserving a degree of their virulence activity (Kunkeaw et al, 2010), which continues the theme of an arms race in the coevolution of Pst and tomato.…”
Section: Discussionmentioning
confidence: 99%
“…Samples for quantitative PCR were collected 6 h post inoculation. To analyze effector expression from Pto DC3000, bacteria were grown overnight in hrp-inducing minimal medium, and proteins were harvested as described previously (Kunkeaw et al, 2010).…”
Section: Bacterial Inoculations and Growth Curve Analysesmentioning
confidence: 99%